Hungarian Monitoring, 31 January 1988 . [Magyar rádiófigyelő], 1988. január 31 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Kohl's visit to Prague - Mubarak in Washington - Situation in Israel still tense Domestic Affairs: - Interview with György Marosán - Young economists' conference in Salgótarján - Social committee to supervise disposal of dangerous pharmaceutical waste - Social and health situation of the elderly - Moving World: how the film magazine is put together - Museum of Military History and the catastrophe of the 2nd Hungarian Army at the Don River Economy: - Debate on the future of agriculture Külpolitika: - Kohl prágai látogatása - Mubarak Washingtonban - Izraelben változatlanul nyugtalan a helyzet Belpolitika: - Marosán György interjú - Fiatal közgazdászok salgótarjáni tanácskozása - Társadalmi bizottság a gyógyszergyári veszélyes hulladékok megsemmisítésének ellenőrzésére - Időskorúak szociális, egészségügyi helyzete - Mozgó Világ: a magazin összeállításának műhelytitkai - A Hadtörténeti Múzeum és a második magyar hadsereg doni katasztrófája Gazdaság: - Vita a mezőgazdaság jövőjéről